2017
DOI: 10.1161/circheartfailure.117.003850
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure–Related Hyperphosphorylation in the Cardiac Troponin I C Terminus Has Divergent Effects on Cardiac Function In Vivo

Abstract: Background In human heart failure, Ser199 (equivalent to Ser200 in mouse) of cardiac troponin I (cTnI) is significantly hyper-phosphorylated and in vitro studies suggest it enhances myofilament calcium sensitivity and alters calpain-mediated cTnI proteolysis. However, how its hyper-phosphorylation affects cardiac function in vivo remains unknown. Methods and Results To address the question, two transgenic mouse models were generated: a phospho-mimetic cTnIS200D and a phospho-silenced cTnIS200A, each driven b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
(52 reference statements)
1
5
0
Order By: Relevance
“…In the model of HOCl-induced oxidative damage, EA can reduce the damage to vascular endothelial function in WT mice, but it cannot protect the vascular endothelial tissues in Nrf2 knockout mice. This result further confirmed that Nrf2 is a key protein involved in the antioxidant effect of EA [21,22]. By investigating the effect of EA on AS in mice, this study showed that EA exerted a protective effect against stroke and atherosclerosis in humans.…”
Section: Detection Of Vasodilation Functions In Micesupporting
confidence: 73%
“…In the model of HOCl-induced oxidative damage, EA can reduce the damage to vascular endothelial function in WT mice, but it cannot protect the vascular endothelial tissues in Nrf2 knockout mice. This result further confirmed that Nrf2 is a key protein involved in the antioxidant effect of EA [21,22]. By investigating the effect of EA on AS in mice, this study showed that EA exerted a protective effect against stroke and atherosclerosis in humans.…”
Section: Detection Of Vasodilation Functions In Micesupporting
confidence: 73%
“…Neonatal rat ventricular myocyte studies. Neonatal rat hearts were isolated from 0-1-day-old Sprague-Dawley rat pups (Charles River Laboratories), placed in icecold Krebs-Henseleit Buffer (KHB) 56 , and rinsed twice. Next, the atria were removed, and the isolated ventricles were digested in 37°C KHB supplemented with 1 g:100 mL collagenase type-II (Worthington) and 0.05% trypsin with intermittent stirring.…”
Section: Methodsmentioning
confidence: 99%
“…Muscle contraction and its molecular motor myosin are regulated through the phosphorylation of cardiomyocyte cytoskeletal proteins, such as the regulatory myosin light chain (MLC2). Decreased levels of phosphorylated MLC2 (MLC2-P) have been observed in HF [19,20]. HF top-down quantitative proteomics has identi ed the phosphorylation of cardiac troponin I (cTnI) as a candidate biomarker for chronic HF [21].…”
Section: Discussionmentioning
confidence: 99%